The GhSWEET42 Glucose Transporter Participates in Verticillium dahliae Infection in Cotton - Sun, Mengxi; Zhang, Zhiqiang; Ren, Zhongying; Wang, Xingxing; Sun, Wenjie; Feng, Hongjie; Zhao, Junjie; Zhang, Fei; Li, Wei; Ma, Xiongfeng; Yang, Daigang (Frontiers in Plant Science, 2021)
The SWEET (sugars will eventually be exported transporter) proteins, a family of sugar transporters, mediate sugar diffusion across cell membranes. Pathogenic fungi can acquire sugars from plant cells to satisfy their nutritional demands for growth and infection by exploiting plant SWEET sugar transporters. However, the mechanism underlying the sugar allocation in cotton plants infected by Verticillium dahliae, the causative agent of Verticillium wilt, remains unclear. In this study, observations of the colonization of cotton roots by V. dahliae revealed that a large number of conidia had germinated at 48-hour post-inoculation (hpi) and massive hyphae had appeared at 96 hpi. The glucose content in the infected roots was significantly increased at 48 hpi. On the basis of an evolutionary analysis, an association analysis, and qRT-PCR assays, GhSWEET42 was found to be closely associated with V. dahliae infection in cotton. Furthermore, GhSWEET42 was shown to encode a glucose transporter localized to the plasma membrane. The overexpression of GhSWEET42 in Arabidopsis thaliana plants led to increased glucose content, and compromised their resistance to V. dahliae. In contrast, knockdown of GhSWEET42 expression in cotton plants by virus-induced gene silencing (VIGS) led to a decrease in glucose content, and enhanced their resistance to V. dahliae. Together, these results suggest that GhSWEET42 plays a key role in V. dahliae infection in cotton through glucose translocation, and that manipulation of GhSWEET42 expression to control the glucose level at the infected site is a useful method for inhibiting V. dahliae infection.